Maternal Diaphragmatic Hernia Correction During Pregnancy - Dandan Shi; Juan Sebastián Barona-Wiedmann; Mauricio Velásquez; Maria Josefa Franco; Henry Muñoz; Albaro José Nieto-Calvache (Maternal-Fetal Medicine)
Abstract. Congenital diaphragmatic hernia consists of a defect in the embryonic development of the diaphragm that allows the passage of the abdominal viscera into the thoracic cavity, its diagnosis during pregnancy is quite rare. We present the case of a 31-year-old woman, with 23 weeks of gestation, who consulted for epigastric pain, nausea, and repetitive emetic episodes, without improvement with the medication provided. Due to the intense abdominal pain, a computed tomography of the abdomen and thorax was performed where the 28 mm defect was found at the left diaphragmatic level with protrusion of the gastric fundus to the thoracic cavity. She was taken to surgical management by laparoscopy with abdominal and thoracic approach, with a successful result and without maternal perinatal complications. Although the integrity of the diaphragmatic suture could be feared in relation to the increase in intraabdominal pressure due to uterine growth, the evolution of our patient and previous reports show that postoperative complications are not frequent. Successful vaginal delivery has even been described in some reports. Diaphragmatic hernias diagnosed during pregnancy are quite rare. We suggest that the optimal management of them during pregnancy is immediate surgical correction in case of persistent symptoms, more studies are needed to establish firm recommendations on the management of this pathology.